Hilirization of Processed Seagrape Products to Improve The Economy of The Lamongan Community: Hilirisasi Produk Olahan Anggur Laut untuk Meningkatkan Perekonomian Masyarakat Kabupaten Lamongan - Nur Mahmudah; Ahmad Shofiyuddin; Moh Mu`Alliful Ilmi; Ifa Khoiria Ningrum (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Sea grapes are a type of seaweed that has high economic value which can be used as food and medicine. Most Paciran people are familiar with sea grapes, but its benefits are limited to fresh food ingredients such as urap-urap. The lack of knowledge and skills related to processed marine grape products requires a comprehensive and productive production of processed marine grape products in order to improve the economy of the people in Paciran Village, Paciran District. The purpose of this community service is to improve the community's economy in improving the level of welfare for the better in Paciran District through training and mentoring of quality and highly competitive sea grape processed products in the form of juice, jelly and sea grape biscuits. The implementation method in community service used is field surveys, coordination with the community, and program implementation through training and mentoring. The results and implications of the community service program which was attended by 55 participants consisting of sea grape cultivators, sea grape processing UMKM and Mrs PKK Paciran Village. These results can be identified through the results of a questionnaire that has been distributed and filled out by Paciran Village residents through training and mentoring. The results of community service have a positive impact on Paciran Village because they have succeeded in adding insight, knowledge and skills about processed wine and can be used as a village center business for processing sea grapes in Paciran Village